VP208 Informing An Economic Model For Hyperhidrosis: A Clinical Survey. (2017) - Stoniute, Julija; Moloney, Eoin; Rice, Stephen; Levell, Nick; Craig, Dawn
Abstract : INTRODUCTION: Hyperhidrosis is characterized by uncontrollable excessive sweating, which occurs at rest, regardless of temperature. As part of a wider study exploring the clinical and cost effectiveness of alternative treatments for primary hyperhidrosis, a survey of United Kingdom (UK) dermatologists was conducted to gain a better understanding of current clinical practice in the area and inform economic model inputs. METHODS: The survey was conducted by means of an online survey tool, "Qualtrics". It was circulated to members of the British Association of Dermatologists. Topics covered included treatments typically administered, medication dosages prescribed, effectiveness of treatments, adverse events related to treatments and resource use associated with individual treatments. RESULTS: Forty-five respondents from forty-two different dermatology units completed the survey. The majority of clinicians (83 percent) prescribed more than one medication - most commonly oxybutynin and propantheline bromide. The next most commonly reported treatments were: iontophoresis, botulinum toxin and curettage. Respondents were asked to indicate dosage, frequency and details about follow-up visits related to medication use. Doses prescribed were largely consistent with British National Formulary (BNF) recommendations. For other treatments, dermatologists were asked to indicate duration of the procedure, job title of the treatment provider and details about monitoring visits. Results were similar to the findings from the literature and previously conducted interviews with clinicians. Respondents were asked to indicate the dropout rates for each type of treatment due to lack of effectiveness and adverse events. Dropout rates were relatively high for both reasons. CONCLUSIONS: The results highlight the wide range of treatments for hyperhidrosis currently administered by dermatologists across the UK, and the variation in current clinical practice. This variation highlights the lack of evidence-based guidance underpinning practice and the importance of clinical surveys as a complement to usual data collection methods.